Meningkatkan Pembelajaran Non Akademik Melalui Permainan Catur Dan Prestasi Belajar Siswa Madrasah Tsanawiyah Diabad 21 - Ratno Susanto Ratno; Achmad Afandi; Nur Khozanah Ilmah (Jurnal Pengabdian Kepada Masyarakat (JPKM) Langit Biru, 2022)
This community service aims to improve non-academic learning through chess extracurriculars. This game of chess means a game played by 2 people which requires high concentration to get the opponent's points. The community dharma method uses training and mentoring for students. This training is held once a week at Madrasah Tsanawiyah Nurul Huda Dau. This assistance means providing motivation in students so that they are enthusiastic about practicing and enhancing student achievement in learning. The results of dharma form learning achievements, both academic and non-academic, the output of chess training which is routinely very crucial in the new era of adaptation. The conclusion is based on the output of this community dharma, hopefully the training and assistance will be useful for students at school, and as a provision for future skills for achievement